Assessment of the appropriateness of stress ulcer prophylaxis use and its determinants among admitted surgical patients at Debre Berhan University Hakim Gizaw Hospital, Ethiopia. A hospital-based cross-sectional study - Tsige, Abate Wondesen; Beyene, Dessale Abate; Wondmkun, Yehualashet Teshome; Endalifer, Bedilu Linger; Habteweld, Habtemariam Alekaw; Gebretadik, Fissha Assegidew; Gebeyehu, Aregahegn Adafir; Azene, Belayneh Abebaw; Alamneh, Misganaw Abebaw; Tesfaye, Daniel Zebene; Fered, Misganaw Aynalem; Girma, Mandefro Teje; et al. (Frontiers in Medicine, 2024)
Introduction Pharmacological stress ulcer prophylaxis (SUP) has been recommended for many years to reduce the risk of clinically significant upper gastrointestinal (GI) bleeding caused by stress ulcers (SUs). Stress-related ulcer bleeding in surgical patients significantly increases morbidity and mortality. Therefore, preventing stress-induced hemorrhage is the most appropriate measure for patients who are at increased risk. However, the inappropriate use of SUP has increased in recent years, and its use in Ethiopian surgical patients has not been well studied. Objective The aim of this study was to assess the appropriateness of SUP use and its determinants among admitted surgical patients at Debre Berhan University Hakim Gizaw Hospital (DBUHGH), Ethiopia. Methods We randomly selected 230 patients from the whole cross-sectional group of all surgical patients at DBUHGH from 1 February to 30 June 2023. The risk of stress ulcer (SU) development was assessed using the modified American Society of Health-System Pharmacists (ASHP) guidelines. For data analysis, we used SPSS version 25. Results The mean age of study participants was 47.2 years (SD ± 20.4), and out of the total of 230, 130 (56.5%) were women. Approximately 66% of study participants took inappropriate SUP based on ASHP guidelines criteria. The most commonly used drug class for SUP was histamine-2 receptor blockers 115 (50%). Study participants who have a Charlson Comorbidity Index Score of moderate and GI bleeding have been significantly associated with the inappropriate use of SUP. Conclusion In our study, inappropriate SUP use was common in the surgical ward of DBUHGH. This may be an area that requires further and more focused working together among clinical pharmacists and medical professionals in an institution-specific SUP protocol that aids clinicians in identifying appropriate candidates for SUP medication.